-5(x-1)=3(x+8)

Simple and best practice solution for -5(x-1)=3(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x-1)=3(x+8) equation:



-5(x-1)=3(x+8)
We move all terms to the left:
-5(x-1)-(3(x+8))=0
We multiply parentheses
-5x-(3(x+8))+5=0
We calculate terms in parentheses: -(3(x+8)), so:
3(x+8)
We multiply parentheses
3x+24
Back to the equation:
-(3x+24)
We get rid of parentheses
-5x-3x-24+5=0
We add all the numbers together, and all the variables
-8x-19=0
We move all terms containing x to the left, all other terms to the right
-8x=19
x=19/-8
x=-2+3/8

See similar equations:

| 2/3(x)-10=-12 | | 5x+8x=47(3)+54  | | 5+3=2x | | 8x-16=128 | | 2(3x+6)=-13+9 | | 5x+6=-7+3x+23 | | -4x+7x=30 | | 3=t-11/2 | | 4(2y-5)=-4 | | d+7/3=3 | | 3.2x+6=10 | | z+7/1=2 | | 3x-15/9=57/4 | | u-12/3=2 | | G(-3)=3x2-3x | | g+3/3=4 | | F(4)=-5x+2 | | 1=v-92/5 | | 7x+4=3x-40 | | 200m-100m+57,000=60,900-200m | | 2+14n=0 | | x/1210=2.15 | | 19=3-2y | | 3(r-13)+2=20 | | r+5/3=1 | | 2b^2+17b=-21 | | 3x-8x=4-19 | | 2.3*x=6.9 | | (7x−5)+(5x+27)=90 | | 3(x-2)-(3x+2)=5(4x+4) | | 2=15-7/8x | | 8+6u=5u |

Equations solver categories